The Complexity of PRC2 Subcomplexes. Issue 8 (August 2019) - van Mierlo, Guido; Veenstra, Gert Jan C.; Vermeulen, Michiel; Marks, Hendrik
Abstract : Polycomb repressive complex 2 (PRC2) is a multisubunit protein complex essential for the development of multicellular organisms. Recruitment of PRC2 to target genes, followed by deposition and propagation of its catalytic product histone H3 lysine 27 trimethylation (H3K27me3), are key to the spatiotemporal control of developmental gene expression. Recent breakthrough studies have uncovered unexpected roles for substoichiometric PRC2 subunits in these processes. Here, we elaborate on how the facultative PRC2 subunits regulate catalytic activity, locus-specific PRC2 binding, and propagation of H3K27me3, and how this affects chromatin structure, gene expression, and cell fate. Highlights: Polycomb repressive complex 2 (PRC2) is a multisubunit epigenetic protein complex that regulates gene expression by catalyzing trimethylation of histone H3 on lysine 27 (H3K27me3), which is essential for embryonic development. PRC2 can associate with a multitude of facultative subunits resulting in at least two different multimeric configurations called PRC2.1 and PRC2.2. However, the exact interplay between the two subcomplexes requires further study. PRC2.1 and PRC2.2 are recruited to target genes via distinct mechanisms and have divergent roles in gene silencing, but their combined action together with PRC1 is required for Polycomb function. Changes of cellular state, such as during the differentiation of embryonic stem cells, can evoke architectural and functional changes in the PRC2 subcomplexes.